Antibiotic Consumption Patterns in European Countries Might Be Associated with the Prevalence of Type 1 and 2 Diabetes - Ternák, Gábor; Németh, Márton; Rozanovic, Martin; Bogár, Lajos (Frontiers in Endocrinology, 2022)
Several publications have raised the issue that development of diabetes preceds alteration of the microbiome (dysbiosis) and the role of environmental factors. Antibiotics induces dysbiosis and the authors wanted to estimate associations between consumption of antibiotics and the prevalence of diabetes (Type-1, /T1D/, Type-2 /T2D/) in european countries. If such association exists, the dominant use antibiotic classes might be reflected in the prevalence of T1D and T2D in different countries. Comparisons were performed between the prevalence of diabetes estimated for 2019 and featured in the Diabetes Atlas with the average yearly consumption of antibiotic classes between 2010-2109, calculated from the ECDC yearly reports on antibiotic consumption in Europe. Pearson correlation and variance analysis were used to estimate the possible relationship. Strong, positive (enhancer) associations were found between the prevalence of T1D and the consumption of tetracycline (J01A /p: 0.001/) and the narrow spectrum penicillin (J01CE /p: 0,006/, CF /p: 0.018/). Strong negative (inhibitor) association was observed with broad-spectrum, beta-lactamase resistant penicillin (J01CR /p: 0.003/), macrolide (J01F /p: 0.008/) and quinolone (J01M /p: 0.001/). T2D showed significant positive associations with cephalosporin (J01D /p: 0.048/) and quinolone (J01M /p: 0.025/), and a non-significant negative association was detected with broad-spectrum, beta-lactamase-sensitive penicillin (J01CA /p: 0.067/). Countries showing the highest prevalence of diabetes (first 10 positions) showed concordance with the higher consumption of “enhancer” and the lower consumption of “inhibitor” antibiotics (first 10 positions) as indicated by variance analysis. Countries with high prevalence of T1D showed high consumption of tetracycline (p: 0.015), and narrow spectrum, beta-lactamase sensitive penicillin (p: 0.008), and low consumption of “inhibitor” antibiotics (broad-spectrum, beta-lactamase resistant, combination penicillin (p: 0.005), cephalosporin (p: 0.036), and quinolone (p: 0.003). Countries with high prevalence of T2D consumed more cephalosporin (p: 0.084), a quinolone (p: 0.054), and less broad-spectrum, beta-lactamase sensitive penicillin (p: 0.012) than other countries. The development of diabetes-related dysbiosis might be attached to higher consumption of specific classes of antibiotics, showing positive (enhancer) associations with the prevalence of diabetes, and the low consumption of other classes of antibiotics shoving negative (inhibitory) associations. Those groups of antibiotics are different in T1D and T2D.